The saint martyrs of Cherson according to the written and archaeological sources - Klenina, E. (Херсонесский сборник, 2006)
Chersonesos in Taurica, situated in the southwest part of Crimea, existed from the late 5th cent. BC to the early 15th cent. AD (Fig. 1). One of the most interesting periods is the time of Christianity acceptance in the 4th cent. AD (Цукерман 1994: 549; Золотарев, Коробков 2002: 69-70). The events are reflected in written sources of the 7th cent. AD (Латышев 1907). The descriptions of the events connected with martyrs and its dating have provoked a great interest for the explorers. However information from the sources is extremely discordant, that handicaps searching of monuments, connected with the Chersonesos martyrs. The archаeological monuments, bound with activity of the martyrs can be divided into two categories: occurring during martyrs lifetime building or then tombs and memorial buildings constructed in the period of immortalizing of the martyrs in the 6th-7th centuries Одним из наиболее интересных периодов существования Херсонеса является время христианизации населения в IV в. Эти события отражены в письменном источнике VII в. Сохранились археологические памятники, которые можно разделить на две группы: сооружения, существовавшие при жизни епископов-мучеников, а также их могилы и мемориальные постройки, появившиеся в период увековечивания их памяти в VI-VII вв. Канонизация первых христианских святых мучеников получила распространение по всей империи в ранневизантийский период.